2008
DOI: 10.1002/iroh.200710971
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate Community Structure in Three‐Gorges Reservoir, China

Abstract: We investigated the macroinvertebrate community structure in Three-Gorges Reservoir during a three-year period after the reservoir became operational. Comparison with data of previous authors obtained before the damming showed that the benthic community changed drastically in the reservoir. Oligochaetes and chironomids dominate the present community. An apparent annual cycle in the benthic community (expressed as richness, density and community type) was found in the second year, lagging one year behind the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
(25 reference statements)
1
37
0
Order By: Relevance
“…Little is known about the basic ecological information of this species. Some studies showed that they are frequent in Yangtze River, especially in January and April (SHAO et al, 2008;ZHANG et al, 2010). In addition, this study showed that they were dominant in spring.…”
Section: Macroinvertebrates Zonation Pattern Under the Condition Of Hsupporting
confidence: 51%
See 1 more Smart Citation
“…Little is known about the basic ecological information of this species. Some studies showed that they are frequent in Yangtze River, especially in January and April (SHAO et al, 2008;ZHANG et al, 2010). In addition, this study showed that they were dominant in spring.…”
Section: Macroinvertebrates Zonation Pattern Under the Condition Of Hsupporting
confidence: 51%
“…In the Xiangxi Bay, chironomids had relatively higher abundances in the first year after the impoundment of TGR, but from August 2004, oligochaetes became the dominant group (relative abundance of total density over 90%), with the highest density in the middle reach (SHAO, 2008). Compared to that in the 1st stage (over 15000 ind/m 2 in April 2006, estimated from SHAO (2008)), the macroinvertebrate density of the bay declined dramatically from the 2nd impoundment stage, but the dominance of oligochaetes was not affected.…”
Section: Macroinvertebrate Community In Different Impoundment Stagesmentioning
confidence: 99%
“…The mainstream and Xiangxi Bay of the reservoir both are main areas ( Fig. 2) of long term ecological observation and research carried out by the Xiangxi Ecosystem Station, Chinese Academy of Sciences and China Three Gorges Project Corporation, and more detailed descriptions of the study areas can be found in the published literature (e.g., Shao et al, 2008;Xu et al, 2009a,c;Zhang et al, 2010).…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…Eutrophication and algal blooms have proven to be stubborn environmental problems all over the world for decades (Schindler, 2006;Smith et al, 2006), and also have become major problems of aquatic ecosystem degradation after many river dammings (Ha et al, 2003). Long-term studies of phytoplankton succession showed increases in algal biomass in many regulated rivers, resulting from increased nutrient inputs coupled with hydrologic changes (Górniak et al, 2003).…”
Section: Algal Bloomsmentioning
confidence: 99%
See 1 more Smart Citation